Psychological Distress and Help-Seeking by Residents of a Neighborhood Naturally Occurring Retirement Community (NNORC). Issue 7 (16th November 2016) - McClive-Reed, Kimberly P.; Gellis, Zvi D.
ABSTRACT: This article presents findings from an annual program survey of residents of a horizontal neighborhood naturally occurring retirement community (NNORC). The study explored the relationship between several factors (age, co-residents, number of chronic illnesses, self-reported health, loneliness, sense of mastery, locus of control, pain, and psychological distress) and their ability to predict general health, level of psychological distress, and the quantity and type of help-seeking behaviors. Although residents generally reported moderate to high levels of chronic disease, pain, loneliness, and concerns about life issues, 25% of them sought no help from any of the listed resources, and 65% sought help from only one of seven resources. The most common source of help for most (70%) was a primary care physician (PCP), and comparatively few respondents sought help from other sources. Older adults, especially those with chronic illness, generally consider their PCP to be the first, and perhaps only, source to consult. However, research indicates that the most effective health promotional programs for older adults are social and educational group activities, rather than individual health-focused interventions. Possible means of redirecting residents toward NNORC services include more vigorous outreach and creating collaborative partnerships between local PCPs serving older populations and the NNORC.